Traditional oral literature and the socialisation of the Shona (Zimbabwe) girl child: an agenda for disempowerment - Chigidi, Willie L.; Tembo, Charles (Africa Institute for Culture, Peace, Dialogue and Tolerance Studies, 2016)
This article looks at the role played by Shona oral art forms in conditioning the girl child for a life of docility and extreme passiveness. It is argued and maintained that certain oral art forms were deliberately crafted to socialize females in a way that would disempower them so as to make them serve the interests of the patriarchal order better. The paper establishes that there is a special category of folktales, proverbs and poems whose net effect is to disempower women either by ‘pursuading’ them to remain a muted, docile, and at worst a people that fail to appreciate the value of the special qualities they were endowed with at creation. The effort to disempower women, it is argued, was meant to keep the independence of the female spirit permanently under check. However, in this paper it is feared that if trends in the globalized world are anything to go by then the efforts to thwart the independence of the female spirit have, by and large, been in vain.